2010
DOI: 10.1167/iovs.09-3823
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the TGF-β1–Induced Profibrotic Response of Anterior and Posterior Corneal Keratocytes In Vitro

Abstract: Purpose To characterize phenotypic differences between anterior and posterior corneal keratocytes following stimulation with the pro-fibrotic agent transforming growth factor-beta1 (TGF-β1) in vitro. Methods Sixteen corneas from healthy felines were obtained immediately post-mortem. Lamellar dissection was performed to separate the anterior and posterior stroma at approximately 50% depth either manually (N=2) or using a Moria microkeratome (300μm head, N=14). Cells from the anterior and posterior stroma were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…As quiescence or cell morphology alterations are not unique to the keratocyte phenotype,5 we corroborated our mechanical findings with traditional qPCR, to examine the gene expression of characteristic markers, specific to a keratocytic genotype. In previous studies lumican,22, 30 keratocan,22, 31 ALDH 3 ,22, 31, 32 Thy‐1,9, 33, 34 α‐SMA,5, 6, 8, 13, 35 fibronectin,5, 36 CD3435 and vimentin37 have all been examined to help to determine and distinguish the differences in gene and protein expression between corneal keratocytes, fibroblasts and myofibroblast phenotypes in vitro . In this study, we chose to monitor the gene expression profiles of four markers, keratocan, ALDH 3 , Thy‐1 and α‐SMA in response to the chemical and topographical cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As quiescence or cell morphology alterations are not unique to the keratocyte phenotype,5 we corroborated our mechanical findings with traditional qPCR, to examine the gene expression of characteristic markers, specific to a keratocytic genotype. In previous studies lumican,22, 30 keratocan,22, 31 ALDH 3 ,22, 31, 32 Thy‐1,9, 33, 34 α‐SMA,5, 6, 8, 13, 35 fibronectin,5, 36 CD3435 and vimentin37 have all been examined to help to determine and distinguish the differences in gene and protein expression between corneal keratocytes, fibroblasts and myofibroblast phenotypes in vitro . In this study, we chose to monitor the gene expression profiles of four markers, keratocan, ALDH 3 , Thy‐1 and α‐SMA in response to the chemical and topographical cues.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this gene served as a marker for keratocyte phenotype. Thy‐1 expression can be induced via the transformation of a corneal karatocytes to corneal fibroblasts or myofibroblasts9 and it is regularly used in corneal tissue engineering applications to help distinguish corneal fibroblasts from keratocytes 9, 33, 34. In addition, corneal wound fibroblasts and myofibroblasts express α‐SMA, which is linked to wound contraction 6, 8, 13.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin and eosin and Masson's trichrome stains were used for analysis of pathologic changes. Immunohistochemical staining for a-SMA and YY1 tissues was performed according to a previous paper (25). The severity of fibrosis was evaluated in stained sections by an individual who was blinded to the genotypes of the mice.…”
Section: Histopathologic and Immunohistochemical Examinationmentioning
confidence: 99%
“…Cells were supplemented with Dulbecco's modified Eagle medium and 10% fetal bovine serum at 378C for 4 days. Anti-a-SMA antibody (1A4; DAKO Cytomation, Carpinteria, CA), anti-collagen (LF-67; Larry W. Fisher, Ph.D., Matrix Biochemistry Section, Craniofacial and Skeletal Diseases Branch of NIH), and anti-YY1 antibody (H-414; Santa Cruz, Santa Cruz, CA) were stained according to a previous paper (25). The cells were examined with a Zeiss fluorescence microscope.…”
Section: Western Blot Analysis and Quantitative Polymerase Chain Reacmentioning
confidence: 99%
“…11,12 The sensitivity of a tissue to inflammatory stimuli is most likely determined, at least in part, by the regional type of fibroblast. 13,30 In this study, we compared the responses of fibroblasts isolated from the cornea, lacrimal gland, and Tenon's capsule, to the proinflammatory cytokine, IL-1␤. We found that, after IL-1␤ stimulation, corneal fibroblasts exhibit heightened proinflammatory cytokine and PGE 2 production relative to lacrimal gland or Tenon's capsule fibroblasts (Figs.…”
Section: Discussionmentioning
confidence: 99%